Optimizing Student Engagement and Performance usingAI-Enabled Educational Tools - Khaizure Mirdad; Ora Plane Maria Daeli; Nanda Septiani; Anita Ekawati; Umi Rusilowati (Pandawan Sejahtera Indonesia, 2024)
Education is the primary pillar in the progress of modern society. With the development of artificial intelligence (AI) technology, its potential to advance the learning process has become a major focus. This research focuses on the integration of AI-based educational tools to enhance student engagement and academic performance. Through experimental design with a control group, students were divided into two groups: one using AI tools while the other followed conventional methods. Students from various educational levels participated in this research. Data were collected through questionnaires and academic evaluations to compare the outcomes between the two groups. Data analysis was conducted using SmartPLS, enabling the evaluation of the impact of AI tools on student learning. The results indicate that AI integration enables a more personalized and responsive approach to the unique needs of students. It is expected that AI technology in education will bring significant changes in how students engage and achieve academic success. This research expands the understanding of the potential of AI in improving the education process. The integration of AI technology in learning is a progressive step toward a more adaptive and effective education system, preparing students for success in an increasingly connected and complex world